Tolerance evaluation and morphophysiological responses of Astronium graveolens, a native brazilian Cerrado, to addition of lead in soil. - Araujo, Maycon A. [UNESP]; Leite, Marilaine C.M. [UNESP]; Camargos, Liliane S. [UNESP]; Martins, Aline R. [UNESP] (Elsevier, 2020)
Since the ecosystem is contaminated by lead, decontamination is a difficult and expensive process. Therefore, an alternative would be the use of phytoremediation plants, which have been studied more intensely in recent decades. Astronium graveolens Jacq (Anacardiaceae) is a Cerrado native species and plants of this biome are known to present adaptations and modifications that keep them in this ecosystem. Our aim was to find the tolerance index of A. graveolens to lead doses and to evaluate the morphophysiological alterations of the species when exposed to the heavy metal. The experiment was carried out in a greenhouse in Ilha Solteira-SP, with a completely randomized design and using lead acetate (Pb(C2H3O2)2) as the source of the heavy metal. Samples of the vegetative organs (roots and leaves) were fixed, subsequently dehydrated in an ethyl series, included in hydroxyethyl methacrylate (Leica Historesin) and sectioned for histological slide assembly and subsequent anatomical analysis. The levels of phenolic compounds, protein, amino acid, ammonia, allantoic acid and allantoin were quantified. We calculated the tolerance index for the species. Significant differences were found in leaf and root tissues anatomy, while in relation to the physiology of A. graveolens, a significant difference was observed when the concentration of total ureids in the roots was evaluated. Pb did not interfere with the survivability of the species. In fact, A. graveolens showed a higher secondary growth in the treatment with higher level of lead.
Keywords: Astronium graveolens; Lead (Pb); Morphophysiological adaptation; Phytoremediation